Behind the scenes: International NGOs’ influence on reproductive healt h policy in Malawi and South Sudan - Storeng, Katerini T.; Palmer, Jennifer; Daire, Judith; Kloster, Maren O. (Global Public Health, 2019)
Global health donors increasingly embrace international nongovernmenta l organisations (INGOs) as partners, often relying on them to conduct political advocacy in recipient countries, especially in controversial policy domains like reproductive health. Although INGOs are the prima ry recipients of donor funding, they are expected to work through nati onal affiliates or counterparts to enable ‘locally-led’ change. Using prospective policy analysis and ethnographic evidence, this paper exam ines how donor-funded INGOs have influenced the restrictive policy env ironments for safe abortion and family planning in South Sudan and Mal awi. While external actors themselves emphasise the technical nature o f their involvement, the paper analyses them as instrumental political actors who strategically broker alliances and resources to shape poli cy, often working ‘behind the scenes’ to manage the challenging circum stances they operate under. Consequently, their agency and power are h idden through various practices of effacement or concealment. These pr actices may be necessary to rationalise the tensions inherent in deliv ering a global programme with the goal of inducing locally-led change in a highly controversial policy domain, but they also risk inciting s uspicion and foreign-national tensions.